Molecular Imaging and Radionuclide Therapy of Melanoma Targeting the Melanocortin 1 Receptor - Chengcheng Zhang PhD (Molecular Imaging, 2017)
Melanoma is a deadly disease at late metastatic stage, and early diagnosis and accurate staging remain the key aspects for managing melanoma. The melanocortin 1 receptor (MC1 R) is overexpressed in primary and metastatic melanomas, and its endogenous ligand, the α-melanocyte-stimulating hormone (αMSH), has been extensively studied for the development of MC1 R-targeted molecular imaging and therapy of melanoma. Natural αMSH is not well suited for this purpose due to low stability in vivo. Unnatural amino acid substitutions substantially stabilized the peptide, while cyclization via lactam bridge and metal coordination further improved binding affinity and stability. In this study, we summarized the development and the in vitro and in vivo characteristics of the radiolabeled αMSH analogues, including 99m Tc-, 111 In-, 67 Ga-, or 125 I-labeled αMSH analogues for imaging with single-photon emission computed tomography; 68 Ga-, 64 Cu-, or 18 F-labeled αMSH analogues for imaging with positron emission tomography; and 188 Re-, 177 Lu-, 90 Y-, or 212 Pb-labeled αMSH analogues for radionuclide therapy. These radiolabeled αMSH analogues showed promising results with high tumor uptake and rapid normal tissue activity clearance in the preclinical model of B16F1 and B16F10 mouse melanomas. These results highlight the potential of using radiolabeled αMSH analogues in clinical applications for molecular imaging and radionuclide therapy of melanoma.